The Revenge of Conscience in John Grisham’s A Time to Kill: Psychoanalytic Study - Al-khazaali, Mahmood Hasan. Zaghair (Al-Adab Journal, 2022)
This research paper presents the main theme of the revenge of conscience in John Grisham’s A Time to Kill (1989) is connected with the law especially when the law is misused by statesmen according to many causes such as an identity problem, judicial, racism, and black people oppression in the American community. The aim of the study is too dependent upon the psychology field according to Freud’s personality psychoanalytic theory (1923). The protagonist of the novel who is Carl Lee Hailey (Samuel L. Jackson), decides to take his own right after the law fails to convict the two murderers (Cobb and Willard ) who raped his ten-year-old daughter Tonya Hailey and left her on the brink of death. For this reason, Carl lee decides to take the way of revenge against the two white men for his daughter and racist bigotry spread against every black man at a time when the south of the USA considered blacks as second-class citizens which leads to the psychological struggle in Carl lee Hailey’s mind and leads him to take his own right by the revenge of conscientious for the two crimes: raping his daughter and racial oppression.